Le nuove Chiese evangeliche e pentecostali in Italia, senza fissa dimora, esposte a ragionevoli discriminazioni (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa - 2. Il complesso mondo protestante in Italia - 3. Come pensano le istituzioni - 4. Conclusione.The new Evangelical and Pentecostal Churches in Italy, homeless, exposed to reasonable discriminationABSTRACT: The religious geography in Italy is changing. It is not only Islam, and the growth of the parishes of the various Orthodox Churches, that makes the religious panorama more lively. The spread of many and different Evangelical and Pentecostal Churches represent a sign of renewed vitality for the historical minority Churches that refer to the Reformation present for a long time. These new Churches have been able to rely on the hospitality offered by the various Protestant Churches. Another part, perhaps the most substantial, had to wander from one place to another, more or less precarious or resulting, to be able to offer their faithful a religious service worthy of the name. The article focuses on these homeless Churches exposed to the double contingency of being, on the one hand, more easily the target of reasonable discrimination by Regions and local authorities and, for another, without sufficient voice of the many small communities of believers. The public institutions continue to represent the socio-religious reality following the Ptolemaic scheme that considers the existence of a majority religion, Catholicism, versus small religious minorities, without asking whether this perspective can manage the diversity of increasing religious diversities.